2020
DOI: 10.18203/2320-6012.ijrms20204883
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinical pharmacist intervention in chronic obstructive pulmonary disease management

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a common, preventable, and treatable disease characterized by persistent respiratory symptoms and airflow limitation. In 2016, COPD is the third leading cause of death globally and is projected to increase by more than 30% in the next 10 years. The main threat to the prognosis lies in the lack of disease knowledge, poor medication adherence, and health-related quality of life. Clinical Pharmacist is a key profession to improve patient care in COPD man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…(Table-1) A similar observation was found in the study of Nejc Horvat et al which showed COPD was significantly more common in males (67.7%) than in females. 5,15 The structured pharmacist-led intervention significantly improves the medication adherence and quality of life of COPD patients. Based on our study results, 67 (42.95 %) COPD patients were ex-smokers which showed in Table-1 and it is similar to the study of M. R. Khdour et al from Northern Ireland which showed 60% of patients were ex-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…(Table-1) A similar observation was found in the study of Nejc Horvat et al which showed COPD was significantly more common in males (67.7%) than in females. 5,15 The structured pharmacist-led intervention significantly improves the medication adherence and quality of life of COPD patients. Based on our study results, 67 (42.95 %) COPD patients were ex-smokers which showed in Table-1 and it is similar to the study of M. R. Khdour et al from Northern Ireland which showed 60% of patients were ex-smokers.…”
Section: Discussionmentioning
confidence: 99%